Bedload‐Bedrock Contrasts Form Enigmatic Low‐Relief Surfaces of the Pyrenees. Issue 6 (10th March 2023) - Fox, M.; Hoseason, T.; Bernard, T.; Sinclair, H.; Smith, A. G. G.
Abstract: Low‐relief, high‐elevation surfaces in mountain belts highlight the dynamic nature of landscapes and have provided evidence for changes in tectonics and/or climate. Yet quantifying when changes occurred from topographic data is challenging and relationships between erosion rate, lithology and precipitation are complex. In the Pyrenees, low‐relief, high elevation surfaces are found across both plutonic massifs and the surrounding softer rocks and channel steepness values are relatively uniform between these lithologies. This suggests a weak relationship between erosion rate and lithology despite a clear relationship between the drainage network configuration and the location of the plutonic rocks. We explore this conflicting evidence for strength of the relationship between lithology and erosion rate using a landscape evolution model which accounts for the contrast between bedrock and bedload erodibility. This contrast produces dispersed channel steepness values and predicts the in situ development of low‐relief surfaces, under steady forcing conditions. Plain Language Summary: Unusual landscapes provide an indication that processes shaping Earth's surface have changed. In this way, features of the topography can be used to understand the past. However, the processes shaping the surface are complicated. In the Pyrenees, there are unusual, low‐slope topographic features at high elevations, where we would expect to find steep slopes. One explanation of these low‐slope features is that they have recently been uplifted from low elevations to high elevations. This would require large changes in tectonics. Here we explore whether changes in exposed rock type might produce these low‐slope regions. Because there is no clear indication that exposed rock type might lead to changes in the patterns of drainage networks, we suggest that the exposure of different rock types change the bedload of rivers. This evolving bedload produces complex incision patterns, disrupting the river network and producing low‐slope, high elevation surfaces. Key Points: Bedload‐bedrock contrasts allow for a strong lithological control without a clear geomorphic fingerprint Steady state tectonic forcing with variable lithology can produce low‐relief Pyrenean surfaces